Consequences of phosphorylation on the structural and foaming properties of ovalbumin under wet-heating conditions. (June 2019) - Sheng, Long; Ye, Siqi; Han, Ke; Zhu, Guilan; Ma, Meihu; Cai, Zhaoxia
Abstract: In this study, ovalbumin (OVA) was phosphorylated under wet-heating in the presence of sodium tripolyphosphate at pH 6.0 and 60 °C for 1, 2, 3, 4 and 5 h, and the structural and physical properties of phosphorylated OVA (P-OVA) were investigated. The FT-IR spectrum confirmed the covalent attachment of the phosphate group to OVA. New possible phosphate sites (Ser-221, Ser-269, Tyr-281 and Ser-324) were detected by using liquid chromatography in tandem with mass spectrometry. Circular dichroism (CD) spectra demonstrated that P-OVA molecular became more flexible and disordered. The decreased fluorescence intensity indicated that the chromophore microenvironment became more exposed and polar because of conformational changes. The surface hydrophobicity (H0 ) and the absolute value of zeta potential of P-OVA obtained at 5 h was 1.8 and 1.5 times higher than that of N-OVA. Foaming ability (FA) and foaming stability (FS) were enhanced by 1.7 and 4.4 times after wet-heating phosphorylation for 4 h, which were up to 87.0% and 28.5%, respectively. Furthermore, the correlation analysis suggested that FA was significantly correlated to random structure (P < 0.01) and H0 (P < 0.01), and zeta potential was related with FS (P < 0.05). Graphical abstract: Image 102 Highlights: Ovalbumin was phosphorylated by sodium tripolyphosphate under wet-heating. Possible phosphate sites were detected by LC-MS/MS. Structural changes were confirmed by fluorescence and CD spectrum. H0 and the absolute value of zeta potential increased after the phosphorylation. Foaming ability and stability were promoted by phosphorylation.